A centipede toxin causes rapid desensitization of nociceptor TRPV1 ion channel. (30th April 2020) - Zhu, Aiqin; Aierken, Aerziguli; Yao, Zhihao; Vu, Simon; Tian, Yuhua; Zheng, Jie; Yang, Shilong; Yang, Fan
Abstract: The nociceptive transient receptor potential vanilloid 1 (TRPV1) ion channel is a polymodal receptor for multiple painful stimuli, hence actively pursued as a target for analgesic drugs. We identified a small peptide toxin RhTx2 from the Chinese red-headed centipede that strongly modulates TRPV1 activities. RhTx2, a 31-amino-acid peptide, is similar to a TRPV1-activating toxin RhTx we have previously discovered but with four extra amino acids at the N terminus. We observed that, like RhTx, RhTx2 activated TRPV1, but RhTx2 rapidly desensitized the channel upon prolonged exposure. Desensitization was achieved by reducing both the open probability and the single-channel conductance. RhTx2 is not only a tool to study the desensitization mechanism of TRPV1, but also a promising starting molecule for developing novel analgesics. Highlights: A 31-amino-acid peptide RhTx2 from the venom of Chinese red-headed centipede strongly activated TRPV1 channel. RhTx2 rapidly desensitized the TRPV1 channel upon prolonged exposure. RhTx2 reduced single-channel conductance of TRPV1 during desensitization. Computational docking was employed to explore the structural mechanisms underlying RhTx2 binding and channel desensitization.